The Effect of Training, Compensation, and Work Environment on Job Satisfaction and Employee Performance in a Telecommunications Company - Novita Tasya Sabila; Endang Siti Astuti; Benny Hutahayan (PT. Global Research Collaboration, 2026)
Purpose: This study aims to analyze the effect of training, compensation, and work environment on job satisfaction and employee performance in a telecommunications company in East Java, with job satisfaction examined as a mediating variable. Design/Methodology: This research uses a quantitative explanatory approach involving 193 employees in the Prepaid Channel Division of PT Indosat Ooredoo Hutchison. A total of 130 valid responses were obtained through proportionate stratified random sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Findings: The results show that training, compensation, and work environment have a positive and significant effect on job satisfaction and employee performance. Job satisfaction also has a significant positive effect on employee performance and partially mediates the relationship between the independent variables and employee performance. Research Limitations: This study is limited by its cross-sectional design, which does not capture changes in employee perceptions over time, and by its focus on a single organizational unit within one telecommunications company, which may limit generalizability. Originality/Value: The novelty of this research lies in the integration of formative measurement indicators tailored to a post-merger telecommunications context, providing a more detailed decomposition of human resource practices into actionable managerial components rather than treating them as single-dimensional constructs.